Evaluation of Consumers' Aspects on Organic Farming Products by Regions - Mustafa Aslan; Volkan Burucu; Filiz Pezikoğlu; Duygu Aktürk; Bülent Tarım; Sunay Demir; Ayten Aşkın Kılınç; Murat Doğu; Başak Aydın (Journal of Advanced Research in Natural and Applied Sciences)
The main purposes of this study were to analyze the attitude and behavior of the consumers regarding to purchase of the organic food, the socio-economic comparison of the consumers consuming and non-consuming or-ganic food and to determine the organic food consumption in consideration of different regions. This research was carried out by a questionnaire study with 1494 consumers, consuming organic and non-organic products in six regions in accordance with their socio-economic development index values. By making use of average, percentage and cross tables during the analysis of the data obtained, some of the socio-economical characteristics of the consumers were determined. Factor analysis was used to evaluate the attitudes of the producers consuming organic products regarding the organic products. 25.60% of the consumers in the first region, 47.59% of the consumers in second region, 31.33% of the consumers in third region, 20.48% of the consumers in fourth region, 27.11% of the consumers in the fifth region, 13.86% of the consumers in sixth region declared that they were consuming organic food. Associated with showing and alteration according to the regions, the most consumed organic products were, in respectively, egg, fruit, milk, vegetable. While the 91.30% of the consumers that did not consume organic products in the first region, so did the 94.74% of the third region, 92.42% of the fourth region, 94.21% of the fifth region, 95.80% of the sixth region expressed a positive opinion about consuming organic products, this ratio was determined as 78.16% in the second region.